2019
DOI: 10.1186/s12915-019-0626-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome, proteome and draft genome of Euglena gracilis

Abstract: BackgroundPhotosynthetic euglenids are major contributors to fresh water ecosystems. Euglena gracilis in particular has noted metabolic flexibility, reflected by an ability to thrive in a range of harsh environments. E. gracilis has been a popular model organism and of considerable biotechnological interest, but the absence of a gene catalogue has hampered both basic research and translational efforts.ResultsWe report a detailed transcriptome and partial genome for E. gracilis Z1. The nuclear genome is estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
194
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(210 citation statements)
references
References 148 publications
8
194
0
Order By: Relevance
“…A direct BLAST search of the whole transcriptome confirmed that the enzymes of amino acid biosynthesis are indeed present (E. gracilis does not require supplementation by any amino acid when grown autotrophically on minimal medium; Hall & Schoenborn, 1939), but their localisation is nonplastidial, in agreement with the previous in silico prediction (Ebenezer et al, 2019). Only an incomplete serine synthesis pathway was reconstructed, with no identifiable plastidtargeted phosphoserine aminotransferase.…”
Section: Biosynthetic Pathways Embedded In the Euglena Plastidsupporting
confidence: 84%
See 4 more Smart Citations
“…A direct BLAST search of the whole transcriptome confirmed that the enzymes of amino acid biosynthesis are indeed present (E. gracilis does not require supplementation by any amino acid when grown autotrophically on minimal medium; Hall & Schoenborn, 1939), but their localisation is nonplastidial, in agreement with the previous in silico prediction (Ebenezer et al, 2019). Only an incomplete serine synthesis pathway was reconstructed, with no identifiable plastidtargeted phosphoserine aminotransferase.…”
Section: Biosynthetic Pathways Embedded In the Euglena Plastidsupporting
confidence: 84%
“…We also identified 74/83 (89%) and 113/ 131 (86%) high-confidence plastid-targeted candidates from two earlier studies (Durnford & Gray, 2006; Z ahonov a et al, 2018; Dataset S2), indicating concordance approaching 90%. It is also of relevance that the plastids analysed here were from light-grown cells only, and previous work has demonstrated that significant changes to protein composition are not accompanied by transcript changes: some proteins are therefore probably absent from the present plastid material (Ebenezer et al, 2019). This could arise partially as a result of N-terminal sequence truncation but could also signify our incomplete understanding of euglenid plastid-targeting signals.…”
Section: A Plastid Proteome For E Gracilismentioning
confidence: 87%
See 3 more Smart Citations